PENGARUH GAYA HIDUP TERHADAP PENGGUNAAN CREAM PEMUTIH WAJAH PADA MAHASISWA JURUSAN ANALIS KESEHATAN POLTEKKES KEMENKES RI MEDAN - Setiyawati, Dewi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2014)
The widespread cosmetic use influenced by the life style of community recently has caused the increasingincident of skin disease or disorder due to the use of cosmetic. The incident of skin disorder, among otherthings, is caused by the wrong or excessive use of cosmetic, the poor cosmetic process, and the inappropriateuse of active ingredients in cosmetics. This condition is the background of this study. The purpose of thisexplanatory survey study with the description of causal relationship between the variables throughhypothesis testing was to analyze the influence of life style on the use of whitening facial cream by thestudents of Health Analyst Department of Health Polytechnic, Ministry of Health, Republic of Indonesia,Medan. The population of this study was all of the 239 students in the Health Analyst Department of HealthPolytechnic, Ministry of Health, Republic of Indonesia, Medan. The result of this study with 4 (four)variables on 76 respondents using the whitening facial cream showed that 55 respondents (72.4%) used thewhitening facial cream because of the factors of knowledge, 56 respondents (73.7%) because of students’attitude, 41 respondents (53.9%) because of peer influence, and 46 respondents (60.5%) because of mediainfluence. The result of statistical test using Chi-square test at α = 95% (p < 0.05) showed that there was theinfluence of life style on the use of whitening facial cream in the students in the Health Analyst Department ofHealth Polytechnic, Ministry of Health, Republic of Indonesia, Medan in which the factors of knowledge (p =0.027 < 0.05), peer influence (p = 0.012 < 0.05), and media influence (p = 0.004 < 0.05). However, theresult of the second multivariate test showed that media influence had the most dominant and significantinfluence (p = 0.004 < 0.05) with B = 2.069 and the factor of attitude did not have any influence at all (p =0.275 > 0.05). Community members are suggested to be alert in choosing and using the cosmetics withwhitening cream. The desire to looking beautiful should not be materialized by using any product that canbring bad impact to your face. Good eating pattern and healthy life can help make your skin and bodysmooth. If you want to use whitening facial cream, you may use the one which has been analyzed and testedby BPOM (Drugs and Food Control Agency). The prohibited certain brands can be found out in the mediaor releases issued by BPOM (Drugs and Food Control Agency).